HOTEL INFORMATION TECHNOLOGY ADOPTION: THE CASE OF THE PHILIPPINES - EDIESER L. DE LA SANTA; MYRA VINA D. AGATEP (ASEAN Journal on Hospitality and Tourism, 2005)
This paper attempted to examine the extent of use of information technology among Philippine hotels, their speed in adopting technology, the degree to which these hotels actually use new technology; and to investigate factors that influence their decision to adopt or not technology. The study found that Philippine hotels, though quite late in technology adoption, own a mix of information technologies that appear to slant towards improving guest service. The intrinsic characteristics of technology seem to be the main factor in the decision to adopt technology while IT illiteracy and the prohibitive cost are the main reasons for non-adoption. The research likewise affirmed that ownership structure and firm size positively affect adoption behavior. The results manifest organizational rationalism and recognize the power of social and cultural forces to shape IT adoption behavior. Possible implications were raised regarding strategies that address IT literacy and cost, and enhancing absorptive capacity of small hotels.